The technological model of operating area by the combined transport - Cempírek, Václav; Široký, Jaromír; Císařová, Hana (Univerzita Pardubice, 2010)
The contribution deals with design technology service model using the combined transport. It assesses the performance indicators in relation to price and quality of services provided and on this basis decides on the type of the transport. This is the decision-making processes, which should answer the question, whether used directly in road freight transport, direct rail freight transport or combined transport. In this contribution is the combined transport meant as a system between the conventional modes, which are transhipped goods from road vehicles to the rail cars or river boats.
Keywords: hub location; heuristic and metaheuristic methods; combined transport